(untitled) (Research, Society and Development, 2021)
Objective: The present research performed a clinical and histopathological analysis of female genital schistosomiasis (FGS) cases. This was a descriptive and retrospective study, with a quantitative approach based on secondary databases belonging to Memorial Nestor Piva from Universidade Tiradentes. Methodology: Medical records and biopsies from patients affected with genital schistosomiasis (1984-1994) 75 pathology reports were found, biopsies of feminine genitals, with the respective paraffin blocks and slides. In these three search blocks, to contain sufficient quantity of biological material underwent histological new. For pathological analysis, hematoxylin-eosin, picrosirius Red and Masson’s trichrome staining were used. A distribution of cases per year was performed to obtain an average and a percentage distribution among the most affected organs. In addition, the chi-square test was used to establish an association between schistosomiasis and its anatomical location and with other pathologies. Results: An average of four cases per year was obtained and the infection was found in all genital system organs, with its highest concentration in the ovaries followed by the uterus. In addition, there was an association between the parasitosis and cervical metaplasia, uterine tumors and salpingitis. In the histopathological analysis, several granulomas containing Schistosoma mansoni eggs, in productive and curing phases, were observed. Conclusion: It was concluded that ovaries were the most affected anatomical sites and that the presence of genital schistosomiasis may favor the occurrence of associated pathologies, thus causing a high morbidity rate to women’s health.